Towards a simple global-standard bioassay for a key ecosystem process: organic-matter decomposition using cotton strips. (November 2019) - Colas, F.; Woodward, G.; Burdon, F.J.; Guérold, F.; Chauvet, E.; Cornut, J.; Cébron, A.; Clivot, H.; Danger, M.; Danner, M.C.; Pagnout, C.; Tiegs, S.D.
Highlights: Cotton-strip assays indicate the capacity of ecosystems to decompose organic matter. These assays are sensitive to environmental conditions and environmental stressors. Calibrations among cotton-strip assays enable expression of decomposition rates in a 'common currency'. Microbial communities are similar among cotton-strip assays, and to more-complex substrates (e.g., leaf litter). The cotton-strip assay holds promise as a way to track the impacts of global change on carbon cycling. Abstract: Cotton-strip bioassays are increasingly used to assess ecosystem integrity because they provide a standardized measure of organic-matter decomposition – a fundamental ecosystem process. However, several different cotton-strip assays are routinely used, complicating the interpretation of results across studies, and hindering broader synthesis. Here, we compare the decay rates and assemblages of bacteria and fungi colonizing the three most commonly used cotton materials: Artist's canvas, Calico cloth, and Empa fabric. Cotton strips from each material type were incubated in 10 streams that span a wide range of physicochemical properties across five ecoregions. Additionally, to evaluate responses to environmental stress without potentially confounding biogeographical effects, we deployed identical bioassays in five streams across an acidification gradient within a single ecoregion. Across all streams decomposition rates (as tensile strength loss [TSL]) differed among the three cotton materials; Calico cloth decomposed fastest (time to 50% TSL [T50 ] = 16.7 d), followed by the Empa fabric (T50 = 18.3 d) and then Artist's canvas (T50 = 21.4 d). Despite these differences, rates of TSL of the three cotton materials responded consistently to variation in environmental conditions; TSL of each fabric increased with stream temperature, dissolved-nutrient concentrations and acid-neutralizing capacity, although Artist's canvas and Calico cloth were more sensitive than Empa fabric. Microbial communities were similar among the materials, and values of community structure (e.g., phylotype richness and diversity) were comparable to those reported for decaying leaves in streams from the same region, the major natural basal carbon resource in forested-stream ecosystems. We present linear calibrations among pairs of assays so that past and future studies can be expressed in a "common currency" (e.g., Artist's-fabric equivalents) 'past and future studies' repeated two times in the sentence. Lastly, given its relatively low within-site variability, and the large number of streams where it has been used (>700 across the globe), we recommend Artist's fabric for future work. These results show that cotton provides an effective and realistic standardized substrate for studying heterotrophic microbial assemblages, and acts as a reasonable proxy for more chemically complex forms of detritus. These findings add to growing evidence that cotton-strip bioassays are simple, effective and easily standardized indicators of heterotrophic microbial activity and the ecosystem processes that result.